Morphogen gradients. A question of time or concentration? - Pages, F.; Kerridge, S. (Trends in Genetics, 2000)
Morphogens are secreted proteins that organize surrounding tissues into distinct territories and are thought to act as a function of a threshold of their concentration. Although it has been demonstrated that morphogens act directly on the cells and do not rely on secondary signalling relays, intracellular sequential induction mechanisms, which are dependent on a simple signalling instruction, have not been excluded. Here, we present an alternative model to account for the organizing properties of morphogens, and propose that initial exposure to signalling changes cell context, which in combination with continuing morphogen activity, results in the expression of novel targets.